Deep Education - Francois Victor Tochon (Universidad de Granada, 2010)
This theoretical essay is to clarify what could be a deeper approach to education and its characteristics. The deep approach is a broad phenomenon that encompasses several domains. It manifest a turning point in the way we reflect on a variety of disciplines such as ecology, economy, engineering, mathematics, cross-cultural communication, psychology, and languages. The trend is influenced by semiotics-the science of meaningful signs-as an overarching discipline, process philosophy and complexity theory to address ontological dualism. The deep approach is an applied trend that is revolutionizing the ways we think about what should be accomplished in Education and Teacher Education, and how it should be done.It defines a move towards deeper conceptions of curricula in any disciplines and towards curriculum interconnectedness.